Predicting fracture behavior of quasi-Brittle materials using quantitatively varied geometric specimens: A design method - Junfeng Guan; Yue Ma; Chaopeng Xie (Materials & Design, 2023)
Fracture toughness (KIC) and tensile strength (ft) are two important parameters for describing the fracture performance of quasi-brittle materials. The accurate determination of both parameters is crucial for the safety design and stability evaluation of real engineering structures. A model and method are developed in this paper for simultaneously determining the KIC and ft for quasi-brittle materials without size effects. And using the geometric structural parameter ae as a key design parameter. This method can get KIC and ft to be obtained by fitting curves to any two sets of quantitative specimens with different geometric structures with ae ratio equal to 3. Additionally, fracture full curves and peak load prediction lines with 95% reliability are established for different fracture modes using quantitative design specimens with an ae ratio of 3. These curves and lines can accurately predict fracture behavior and peak loads of large specimens or engineering structures. The proposed design method is verified by combining experimental studies conducted by other scholars on quasi-brittle materials and the simulation results of ABAQUS software. This paper achieves the objective of accurately predicting the fracture properties of quasi-brittle material structures in the field, using quantitative laboratory specimens of various geometries.